Sialic acid transport in Haemophilus influenzae is essential for lipopolysaccharide sialylation and serum resistance and is dependent on a novel tripartite ATP-independent periplasmic transporter. - Severi, E; Randle, G; Kivlin, P; Whitfield, K; Young, R; Moxon, R; Kelly, D; Hood, D; Thomas, G (2005)
Sialylation of the lipopolysaccharide (LPS) is an important mechanism used by the human pathogen Haemophilus influenzae to evade the innate immune response of the host. We have demonstrated that N-acetylneuraminic acid (Neu5Ac or sialic acid) uptake in H. influenzae is essential for the subsequent modification of the LPS and that this uptake is mediated through a single transport system which is a member of the tripartite ATP-independent periplasmic (TRAP) transporter family. Disruption of either the siaP (HI0146) or siaQM (HI0147) genes, that encode the two subunits of this transporter, results in a complete loss of uptake of [14C]-Neu5Ac. Mutant strains lack sialylated glycoforms in their LPS and are more sensitive to killing by human serum than the parent strain. The SiaP protein has been purified and demonstrated to bind a stoichiometric amount of Neu5Ac by electrospray mass spectrometry. This binding was of high affinity with a Kd of approximately 0.1 microM as determined by protein fluorescence. The inactivation of the SiaPQM TRAP transporter also results in decreased growth of H. influenzae in a chemically defined medium containing Neu5Ac, supporting an additional nutritional role of sialic acid in H. influenzae physiology.